Social networks, social satisfaction and place attachment in the neighborhood - Minou Weijs-Perrée; Pauline van den Berg; Theo Arentze; Astrid Kemperman (REGION, 2017)
Feeling socially integrated and being satisfied with one's social life are important indicators for happiness and well-being of individuals and for the strength of local communities. The effect of the living environment on social networks and the importance of local social contacts in the neighborhood has been addressed by many studies. However, social satisfaction has received little attention in these studies. The aim of this study is to describe and predict the effect of personal and neighborhood characteristics on social satisfaction mediated by the impact of place attachment and neighborhood networks. A path analysis is used based on survey and diary data collected between April and May 2014 in Eindhoven and surroundings in the Netherlands among 177 respondents. Results show that social characteristics of the neighborhood play an important role in explaining social satisfaction of individuals. In addition, results confirm the importance of participating in social activities and walking or cycling in the neighborhood.
Keywords: 330; Social satisfaction; place attachment; local social network; neighborhood